Challenges and opportunities for restoration of high-elevation Andean peatlands in Ecuador - Esteban Suarez; Segundo Chimbolema; Ricardo Jaramillo; Leo Zurita-Arthos; Paul Arellano; Rodney A. Chimner; John S. Stanovick; Erik A. Lilleskov (Mitigation and Adaptation Strategies for Global Change, 2022)
Páramo peatlands are a regional reservoir of biodiversity and ecosystem services, accumulating large amounts of carbon and buffering water flows. Despite their importance, they have a long history of use and impacts including drainage for agriculture and grazing, and water withdrawal for human uses. Here we present a preliminary assessment of the conservation status of páramo peatlands in Ecuador and, using a case study, discuss peatland restoration as a tool for mitigation and adaptation to the impacts of current climate change. Through a simple index assessing the cumulative presence of signs of human activities on 163 peatland sites, we found that the level of impact was higher for peatlands located in the Western branch of the cordillera, whereas current human population density, precipitation, and elevation were not significant predictors of the levels of impact. Also, starting in 2017, we implemented a pilot restoration initiative on a 21-ha peatland which had been drained and converted into pasture for at least 150 years. The restoration consisted of two ditch blocking techniques implemented to stop fast-moving water and promote the rewetting of the peatland. During the next 3 years, water table increased from 27 ± 3 cm below the soil surface to 7 ± 1 cm by 2021, while wetland plant communities are colonizing and closing the pools in the blocked ditches. Re-wetting of the peatland has led to an increase in the abundance of native species. This case study suggests that restoration initiatives are an efficient and cost-effective approach to a better management of páramo peatlands, with high potential as a tool for mitigation and adaptation to climate change.

Multidate, multisensor remote sensing reveals high density of carbon‐rich mountain peatlands in the páramo of Ecuador - John A. Hribljan; Esteban Suarez; Laura Bourgeau‐Chavez; Sarah Endres; Erik A. Lilleskov; Segundo Chimbolema; Craig Wayson; Eleanor Serocki; Rodney A. Chimner (Global Change Biology, 2017)
Tropical peatlands store a significant portion of the global soil carbon (C) pool. However, tropical mountain peatlands contain extensive peat soils that have yet to be mapped or included in global C estimates. This lack of data hinders our ability to inform policy and apply sustainable management practices to these peatlands that are experiencing unprecedented high rates of land use and land cover change. Rapid large‐scale mapping activities are urgently needed to quantify tropical wetland extent and rate of degradation. We tested a combination of multidate, multisensor radar and optical imagery (Landsat TM / PALSAR / RADARSAT ‐1/ TPI image stack) for detecting peatlands in a 2715 km 2 area in the high elevation mountains of the Ecuadorian páramo. The map was combined with an extensive soil coring data set to produce the first estimate of regional peatland soil C storage in the páramo. Our map displayed a high coverage of peatlands (614 km 2 ) containing an estimated 128.2 ± 9.1 Tg of peatland belowground soil C within the mapping area. Scaling‐up to the country level, páramo peatlands likely represent less than 1% of the total land area of Ecuador but could contain as much as ~23% of the above‐ and belowground vegetation C stocks in Ecuadorian forests. These mapping approaches provide an essential methodological improvement applicable to mountain peatlands across the globe, facilitating mapping efforts in support of effective policy and sustainable management, including national and global C accounting and C management efforts.